IMPLEMENTASI PENDIDIKAN KARAKTER AKHLAK MULIA PADA SEKOLAH MENENGAH PERTAMA BERBASIS ASRAMA DI TUBAN - Arif Unwanullah (FKIP Unirow Tuban, 2019)
Caracter good manner education tends to emphasize on knowledge but weak on attitude and its application. The phenomenon of students do juvenile delinquency, promiscuity, and abuse of drugs. Islamic boarding schools with integrating curriculum of national and local /manhaj tarbiyah emphasizes on Islamic religion subjects and good manner values to students. However, many schools have not succeded in managing good manner education yet. This study is aimed to know and find out data about planning, implementation, evaluation, and management school boarding of good manner eduction as a case study of qualitative research in SMP boarding system basic inTuban. The study finds that the planning program is formulated in school vision and mission, gol, standart graduation, develop integrated curriculum, and actualizes in active learning process, develop students’ extra activity, religious habit and leadership. Evaluation conducted on whole activities continuously. The success of managerial implementation has been indicated by students’ attitude changes such as disciplinary, obedience, learning achievement, and less violence. For making effective good manner education program should involve of parents community, togetherness and commitment.